2020
DOI: 10.3390/ma13194242
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Cutting Parameters and Tool Geometry for Multi-Criteria Optimization of Surface Roughness and Vibration via Response Surface Methodology in Turning of AISI 5140 Steel

Abstract: AISI 5140 is a steel alloy used for manufacturing parts of medium speed and medium load such as gears and shafts mainly used in automotive applications. Parts made from AISI 5140 steel require machining processes such as turning and milling to achieve the final part shape. Limited research has been reported on the machining vibration and surface roughness during turning of AISI 5140 in the open literature. Therefore, the main aim of this paper is to conduct a systematic study to determine the optimum cutting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(57 citation statements)
references
References 55 publications
0
56
0
1
Order By: Relevance
“…There were other studies [62,67] which indicated the most important parameters were depth of cut on the temperature increase and TW progression. In [31,39,48,[61][62][63][64][65][66][67][68], it was reported that a correlation between cutting temperature and TW was found, mostly triggered by cutting conditions and cutting speed. Temperature based measurement provided significant contribution for detecting TW progress and El Hakim et al [39] indicated that in hard turning of high alloy steel with secondary hardening operation, temperature and flank TW demonstrated an increasing trend.…”
Section: Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…There were other studies [62,67] which indicated the most important parameters were depth of cut on the temperature increase and TW progression. In [31,39,48,[61][62][63][64][65][66][67][68], it was reported that a correlation between cutting temperature and TW was found, mostly triggered by cutting conditions and cutting speed. Temperature based measurement provided significant contribution for detecting TW progress and El Hakim et al [39] indicated that in hard turning of high alloy steel with secondary hardening operation, temperature and flank TW demonstrated an increasing trend.…”
Section: Temperaturementioning
confidence: 99%
“…Monitoring of tool condition is a constraining and unstable process in machining operations [ 31 ]. TW is both inevitable and necessary for chip removing and manufacturing new product.…”
Section: Indirect Tool Condition Monitoring Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example may be the ANOVA analysis [17] or the Monte Carlo method [18]. The ANOVA method is also used for multi-criteria optimization of the manufacturing process, in which the machinability indicator is not only surface roughness but also, for example, the vibration of the machining system [19]. Another example of optimization is the use of a hybrid WOA (Whale Optimization Algorithm) algorithm.…”
Section: Wavelet Analysismentioning
confidence: 99%